The Life and Strange Surprising Adventures of Robinson Crusoe - Defoe, Daniel; Retold by Mowat, Diane; Illustrated by Williams, Anthony (New York Oxford University Press, 2008)
Suitable for younger learners Word count 6,830 Bestseller
Keywords: Crusoe, Robinson (Fictitious character) -- Adventure stories